Oxidative stress factors in Nigerians with rheumatoid arthritis - H., Yeldu M.; G., Arinola O. (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatoid arthritis (RA) is a chronic progressive inflammatory autoimmune disorder characterized by symmetric erosive synovitis and sometimes with multi-system involvement. But the exact mechanism of the disease is not fully understood. In the light of above explanation, the present study measured the plasma levels of total peroxide potential (TPP), total antioxidant potential (TAP), malondialdehyde (MDA), oxidative stress index (OSI) and nitric oxide (NO) in relation to the titer of rheumatoid factor among RA patients compared with controls. Methods: This study included 28 rheumatoid arthritis patients and 28 apparently healthy subjects as controls who were matched for age (50-60 years), sex, and socioeconomic status. Rheumatoid factor was estimated using latex method as described by manufacturer. Anthropometric parameters and plasma levels of TPP, TAP, OSI, MDA and NO were determined using standard techniques. Results: The result indicated that with the exception of mean body weight which was significantly (p<0.001) higher among RA patients (90.61±2.02 years) as compared with controls (77.91±2.51 years), mean age, height and body mass index of RA patients (55.68±1.05kg, 1.65±0.01m and 33.40±0.83 kg/m2 respectively) were not significantly different compared with controls (54.07±1.04kg, 1.61±0.02m and 30.44±1.28 kg/m2 respectively). Plasma TPP, NO, OSI and MDA were significantly (p<0.01; p<0.001) higher while, plasma TAP is significantly lower among RA patients compared with controls. Plasma MDA was positively correlated with titer of rheumatoid factor in the RA patients. Conclusions: Our findings therefore may raise the concept that there are some yet unknown key events in the pathogenesis of RA determination of sex of the skull along with other parameters.